FROM PLATFORMIZATION TO DIGITAL BORDERLANDS: GENERATIVE AI, BOUNDARY OBJECTS, AND THE EXPANSION OF THE DIGITAL LANDSCAPE - Fonseca, Paulo F. C.; Bitencourt, Elias C. (AoIR Selected Papers of Internet Research, 2026)
This paper proposes an analytical shift from platformization to digital borderlands to account for the transformations introduced by generative AI. While digital infrastructures have been central to platformization, generative AI systems do not merely extend these structures but reconfigure and traverse them in ways that may destabilize their original logics. We argue that generative AI functions as a boundary object (Star, 1988, 2010), moving across socio-technical domains with interpretative flexibility while remaining anchored in infrastructural constraints. This mobility enables its integration into diverse fields—creative industries, governance, automation—where its meaning and practical implications are continually renegotiated. To analyze these dynamics, we expand on Fornäs et al. (2003) to propose digital borderlands as a conceptual framework. Unlike platformziation, which emphasize stability and control, borderlands capture the fluid, contested, and reassembled nature of AI diffusion. Digital borderlands foreground the epistemic and infrastructural frictions emerging from generative AI’s movement across legal, institutional, and disciplinary boundaries, producing new governance challenges and socio-technical realignments. By shifting focus from platform control to the negotiation and contestation of AI, this framework provides a critical lens to understand how generative AI not only embeds itself in digital landscapes but also actively reshapes them.